Penerapan Berpikir Kritis Dalam Mengenali Berita Hoaks Di Media Sosial Oleh Generasi Z - Komala Sari; Purwanti Purwanti (CV. ITTC INDONESIA, 2024)
The digital age has significantly transformed how Generation Z accesses and processes information through social media platforms. Platforms like Instagram, Facebook, TikTok, and YouTube have become primary means for disseminating information rapidly and extensively. However, this ease of access also creates opportunities for the spread of hoax news, which can distort public perception and trigger social unrest. This study aims to examine how critical thinking skills can aid Generation Z in identifying and filtering hoax news on social media. Through a qualitative descriptive approach, utilizing a literature review and secondary data analysis, this research outlines steps of critical thinking such as evaluating sources, assessing evidence, fact-checking, and being aware of information biases. The results suggest that critical thinking is not only a vital skill for sorting information, but also a foundational element in fostering effective digital literacy among Generation Z.